INFORMASI FUNDAMENTAL MIKRO DAN MAKRO, RISIKO SISTEMATIS DAN KINERJA SAHAM SETELAH KRISIS GLOBAL - Iis Ismawati (Jurnal Riset Akuntansi Terpadu, 2018)
The objectives of this research are to examine the fundamental factors of macro (the rupiah exchange rates (NTR) and the interest rate of Bank Indonesia Certificate (SBI)) and micro (current ratio (CR), debt to equity ratio (DER), total asset turnover (TATO) and return on assets (ROA), the systematic risk in conjunction with an increase in stock performance manufacturing company in Indonesia stock Exchange after the global crisis. This research used  samples of the sample companies manufacturing industry in Indonesia Stock Exchange. The data used is data that panel cross section data and time series data pre-crisis period (2004-2007) and after the crisis (2009-2013). Sampling using purposive sampling, analytical technique used is multiple regression analysis. The results showed variable micro fundamentals (current ratio (CR), debt to equity ratio (DER), total asset turnover (TATO), return on assets (ROA), after kriris global significant effect on Systematic Risk (RS), variable micro fundamentals (current ratio (CR), debt to equity ratio (DER), total asset turnover (TATO), return on assets (ROA), after crisis global signifikan effect the performance of stocks (KS) the systematic risk (RS) as an intervening variable effect of variable macro fundamentals ((rupiah exchange rates (NTR) and micro fundamental ( debt to equity rati/DER).